Strategi Pengembangan UMKM Melalui Pelatihan Branding Dan Digital Marketing Dalam Peningkatan Pemasaran Produk Di RW 09 Kelurahan Menur Pumpungan - Dhea Amelia Putri Kamila; Roziana Febrianita; Vannia Angelita Yuniar Putri (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The impact of technological developments on the structure of human life is so broad that it has contributed to making changes in various fields, one of which is the economic field. MSMEs as one of the business categories in the economic field are also required to keep abreast of technological developments in order to be able to expand product marketing. MSMEs RW 09 Menur Pumpungan Village as a partner of the 77 KKNT group MBKM UPN "Veteran" East Java is an MSMEs engaged in the food and beverage sector which is still conventional in its marketing efforts so branding and digital marketing are needed. Therefore, the 77 MBKM KKNT group provided counseling and branding assistance with digital marketing which in its method consisted of two stages, namely the implementation stage (FGD, surveys, interviews) and the implementation stage (training and mentoring). The results obtained were that the owners of MSMEs RW 09 felt enthusiastic and attended the counseling given and the 77 MBKM KKNT group successfully provided assistance in the form of product photos, making logos and catalogs, creating Whatsapp Business, and creating Gojek accounts for food pick-up services within Gofood.